2017
DOI: 10.1002/erv.2521
|View full text |Cite
|
Sign up to set email alerts
|

RCT of a Video‐based Intervention Program for Caregivers of Patients with an Eating Disorder

Abstract: The video training is a promising approach and effective supplement for caregivers of patients with an eating disorder. Additional professional help to caregivers increases the effectiveness of the intervention. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The most obvious criticism of this type of skill training is that it is far too brief or nonintensive to effect lasting dyadic change. However, evidence from short‐term and video‐based interventions yield promising findings (Gaudiano et al, ; Quadflieg et al, ; Rex et al, ). When effective, this type of approach should significantly ease dissemination and implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious criticism of this type of skill training is that it is far too brief or nonintensive to effect lasting dyadic change. However, evidence from short‐term and video‐based interventions yield promising findings (Gaudiano et al, ; Quadflieg et al, ; Rex et al, ). When effective, this type of approach should significantly ease dissemination and implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, an experiment investigating how biosocial vulnerabilities for SII are affected by a core therapeutic strategy could provide insight into mechanisms underlying successful treatment, and potentially refine intervention targets (Granic, O'Hara, Pepler, & Lewis, 2007;Hinshaw, 2002). Furthermore, short-term and video-based interventions targeting other problems have each yielded clinically significant posttreatment responses (e.g., Gaudiano, Davis, Miller, & Uebelacker, 2019;Quadflieg, Schädler, Naab, & Fichter, 2017;Rex, Charlop, & Spector, 2018). This study takes a novel approach to understanding parent-child interactions relevant to SII via concurrent assessment of behavioral, affective, and physiological processes during conflict discussions-one where no instruction was provided, and one following a video manipulation teaching GIVE.…”
Section: Physiological Measures and Sii: Respiratory Sinus Arrhythmiamentioning
confidence: 99%
“…Treasure and Nazar () have indicated that the essential features of successful caregiver psychoeducation includes the following: education about the stages of change, information on interpersonal maintenance factors of EDs, and skills for communication and behavioural intervention. Further, interventions are typically delivered in four distinct formats: (a) workshop based (Pépin & King, ; Sepulveda, Lopez, Macdonald, & Treasure, ; Sepulveda, Lopez, Todd, Whitaker, & Treasure, ; Spettigue et al, ; Whitney et al, ), (b) web based (Binford Hopf, Grange, Moessner, & Bauer, ; Hibbs, Rhind, et al, ; Hoyle, Slater, Williams, Schmidt, & Wade, ), (c) through self‐help workbooks (Goddard et al, ; Grover, Naumann, et al, ; Hibbs, Magill, et al, ; Rhind et al, ), or (d) through DVD (Quadflieg, Schädler, Naab, & Fichter, ; Sepulveda, Whitney, Hankins, & Treasure, ). Each mode of intervention has positive impacts on caregivers (Hibbs, Rhind, et al, ) across measures of expressed emotion (Family Questionnaire [FQ] and Level of Expressed Emotion Scale), perception of burden (Eating Disorder Symptom Impact Scale [EDSIS]), anxiety and depression (Hospital Anxiety and Depression Scale and Depression Anxiety and Stress Scale), and accommodation to the illness (Accommodation and Enabling Scale of Eating Disorders).…”
Section: Introductionmentioning
confidence: 99%
“…Dimitropolous et al (2019), along with several others, also extended the application of the existing collaborative carer skills training intervention based on the cognitive interpersonal maintenance model and found the intervention maintains effectiveness across a variety of delivery versions and doses as well as a range of settings (Grover, Naumann, et al, 2011; Grover, Williams, et al, 2011; Jenkins et al, 2018; Magill et al, 2016; Pépin & King, 2013; Quadflieg et al, 2017; Quiles Marcos et al, 2018; Sepúlveda et al, 2019; Whitney, Murphy, et al, 2012). The two most recent of these studies of incorporating social support into treatment for adults examined the implementation of ECHO via trial of low intensity delivery methods including brief (5 hr) carer workshops and/or self‐help via carer information packs or video resources (Keshen et al, 2020; McEvoy et al, 2019).…”
Section: Resultsmentioning
confidence: 94%